2021
DOI: 10.1038/s41380-021-01316-6
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia is defined by cell-specific neuropathology and multiple neurodevelopmental mechanisms in patient-derived cerebral organoids

Abstract: Due to an inability to ethically access developing human brain tissue as well as identify prospective cases, early-arising neurodevelopmental and cell-specific signatures of Schizophrenia (Scz) have remained unknown and thus undefined. To overcome these challenges, we utilized patient-derived induced pluripotent stem cells (iPSCs) to generate 3D cerebral organoids to model neuropathology of Scz during this critical period. We discovered that Scz organoids exhibited ventricular neuropathology resulting in alter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 140 publications
(138 reference statements)
6
55
0
Order By: Relevance
“…Single-cell sequencing revealed that SZ progenitors were specifically depleted of neuronal programming factors. This study suggests that multiple mechanisms in SZ-derived BO converge upon brain developmental pathways and contribute to raising the risk of developing SZ [ 49 ].…”
Section: The Potential Of Induced Pluripotent Stem Cells In Personali...mentioning
confidence: 99%
See 3 more Smart Citations
“…Single-cell sequencing revealed that SZ progenitors were specifically depleted of neuronal programming factors. This study suggests that multiple mechanisms in SZ-derived BO converge upon brain developmental pathways and contribute to raising the risk of developing SZ [ 49 ].…”
Section: The Potential Of Induced Pluripotent Stem Cells In Personali...mentioning
confidence: 99%
“…This approach supports the neurodevelopmental hypothesis of SZ, stating that the disruption of early brain development increases the risk of later manifest psychotic symptoms. Patient-derived iPSCs have proven to be a powerful tool in identifying SZ early neurodevelopmental defects, having revealed alterations in neuronal differentiation [ 45 , 48 , 49 ], migration capacity [ 39 , 43 ], neurite number and length [ 38 , 66 ], synaptic biology [ 47 , 49 , 50 ], connectivity [ 38 ], and neuronal activity [ 41 , 42 , 50 ].…”
Section: The Potential Of Induced Pluripotent Stem Cells In Personali...mentioning
confidence: 99%
See 2 more Smart Citations
“…Impaired neural differentiation and disrupted neuron quantity were observed in schizophrenia patient-derived organoids, compared with the organoids derived from healthy donors. Compared to organoids derived from healthy donors, there are more apoptosis, neural progenitors, in the ventricular zone of schizophrenia patients derived organoids (Notaras et al, 2021a). This is one of the unique advantages of 3D organoids, as brain structures usually do not exist in 2D in vitro neural culture.…”
Section: Brain Organoids Reveal the Genetic Mechanism Of Neural Diseasesmentioning
confidence: 99%